Fattening of mud crab Scylla serrata Forskal in net cages, installed in the drain canal of intensive prawn ponds fed with trash fish and prawn pellet - Kuntiyo (College of Fisheries, University of the Philippines, 1992)
Body weight increment, feed conversion ratio, survival rate, and economic indicators of fattening make and female mud crabs (Scylla serrate) were studied. Feeding treatments were as follows : I, 2% trash fish ; II, 6% trash fish ; III, 10% trash fish ; and IV, 2% commercial prawn pellet of body weight/day. The crabs were cultured in net cages battery (one crab/cell) installed in the drain canal of intensive prawn ponds for 35 days. Result showed Treatment IV to give the highest weight gain (36.90g for male and 23.10g for female crabs) ; this is comparable to Treatment III. The best feed conversion ratio was realized in Treatment I (1.3 : 1 for male and 1.7 : 1 for female crabs). Survival rate for all treatments ranged from 80 to 100%. Treatments III and IV of male crabs and Treatments II, III and IV of female crabs were considered fat as evidenced by the significantly heavier average weight compared t the average weight crabs of equivalent carapace width in previous study conducted by Varikul (1972). Cost and return computations show treatment III to give the hghest net income (B98.17/1.35m3/year), although all Tretanments (male crabs) were profitable (payback period - 1.57, 2.29, 2.59, and 2.75 years for Treatments III, IV, II and I, respectively.